ADSORPSI ASAM LEMAK BEBAS PADA CRUDE PALM OIL MENGGUNAKAN ZEOLIT TERAKTIVASI K2CO3 - Nia Dahlia; Winda Rahmalia; Thamrin Usman (Indonesian Journal of Pure and Applied Chemistry, 2019)
Research on the use of K2CO3-activated zeolite as an adsorbent for free fatty acid (FFA) adsorption on crude palm oil (CPO) has been done. CPO is one of the mainstay products of Indonesian plantations which are used as raw material for cooking oil. The aim of this study to determine the adsorption capacity of activated zeolites against free fatty acid of CPO. The results showed that the iodium uptake capacity of zeolites before activation was 495.6%, activated zeolites were 527.1% and impregnated zeolites were 642.6%. The number of zeolites with the best absorption was 2 grams and ALB was absorbed 4.079% for activated zeolites (ZAA), 4.98% for impregnated zeolites (ZAI), and the water content and impurities were still below SNI standards. The CPO adsorption process with zeolites shows the Langmuir model with a correlation value (R2) of 0.9999 for ZAA and (R2) of 0.9976 for ZAI. The results showed that activated zeolites had lower absorption than impregnated zeolites.